2017
DOI: 10.1007/s11417-017-9260-y
|View full text |Cite
|
Sign up to set email alerts
|

How Strong Is Public Support for the Death Penalty in Singapore?

Abstract: Singapore is well known internationally for its uncompromising stance towards law and order and its use of the death penalty in particular for murder and drug trafficking. Until 2012, it was one of the few countries in the world where the death penalty was mandatory for persons convicted of these two crimes. The law was amended in 2012 to give a judge the choice to impose the death penalty or life imprisonment (with caning) for non-intentional murder and drug trafficking in some situations. What do Singaporean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
0
7
1
Order By: Relevance
“…While some studies (Vito, Keil, & Andreescu, 1999) point out that opposition to the death penalty is more common among the highly educated, others (Thinley & Ziegler Jr, 2020) indicate that education does not affect attitudes toward support for the death penalty. Contrary to previous insights into uninformed public prejudice as a source of public support for the death penalty (Chan, Tan, Lee, & Mathi, 2018;Cochran & Chamlin, 2005), Liu (2021) found that greater support for the death penalty is widespread among the elite. residents with higher education in China.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…While some studies (Vito, Keil, & Andreescu, 1999) point out that opposition to the death penalty is more common among the highly educated, others (Thinley & Ziegler Jr, 2020) indicate that education does not affect attitudes toward support for the death penalty. Contrary to previous insights into uninformed public prejudice as a source of public support for the death penalty (Chan, Tan, Lee, & Mathi, 2018;Cochran & Chamlin, 2005), Liu (2021) found that greater support for the death penalty is widespread among the elite. residents with higher education in China.…”
Section: Discussioncontrasting
confidence: 84%
“…An unavoidable issue in a wide range of scientific studies is the relationship between education and attitudes towards the death penalty (Kuehn, Ridener, & Scott, 2018). Contrary to previous insights into uninformed public prejudice as a source of public support for the death penalty (Chan, Tan, Lee, & Mathi, 2018;Cochran & Chamlin, 2005). Liu (2021) found that greater support for the death penalty was widespread among the elite, ie residents with higher education in China.…”
Section: Literature Reviewmentioning
confidence: 87%
“…An unavoidable issue in a wide range of scientific studies is the relationship between education and attitudes towards death penalty (Kuehn et al, 2018). Contrary to previous insights into uninformed public prejudice as a source of public support for death penalty (Chan et al, 2018;Cochran & Chamlin, 2005), Liu (2021) found that greater support for death penalty was widespread among the elite, i.e. the residents with higher education in China.…”
Section: Literature Reviewmentioning
confidence: 75%
“…While some studies (Vito et al, 1999) point out that opposition to death penalty is more common among the highly educated, others (Thinley & Ziegler, 2020) indicate that education does not affect attitudes toward support for death penalty. Liu (2021) has discovered that stronger promotion of death sentence is widely disseminated among the elite, contrary to earlier insights into ignorant public prejudice as a public source of support for death penalty (Chan et al, 2018;Cochran & Chamlin, 2005). Hessing et al (2003) also referred to the poorly, younger people who defend death sentence in the Netherlands (Kuzina et al, 2020).…”
Section: Discussionmentioning
confidence: 98%
“…Research on public attitudes toward the death penalty has largely focused on samples from the United States (Stack, 2004). Nevertheless, scholars have studied predictors of death penalty support in countries such as Australia (Kelley & Braithwaite, 1990), Bosnia and Herzegovina (Muftic, Maljevic, Mandic, & Buljubasic, 2015), China (Cao & Cullen, 2001; Jiang, Hu, & Lambert, 2018), India (Lambert, Pasupuleti, Jiang, Jaishankar, & Bhimarasetty, 2008), Japan (Jiang, Pilot, & Saito, 2010; Sato, 2017), Mexico (Brown, Benedict, & Buckler, 2010; Updegrove & Orrick, 2018), Singapore (Chan, Tan, Lee, & Mathi, 2018), South Korea (Choi, Jiang, & Lambert, 2017), and the Netherlands (Hessing, de Keijser, & Elffers, 2003), among others. A related body of work has compared and contrasted predictors of death penalty support between international and U.S. samples (Elechi, Lambert, & Ventura, 2006; Jiang, Lambert, & Wang, 2007; Lambert et al, 2016).…”
Section: Introductionmentioning
confidence: 99%